Early iron overload in beta-thalassaemia major: when to start chelation therapy?. Issue 12 (December 1982) - Fargion, S; Taddei, M T; Gabutti, V; Piga, A; Di Palma, A; Capra, L; Fontanelli, G; Avanzini, A
Abstract : Twenty-eight children with beta-thalassaemia major aged between 11 and 48 months were given intensive transfusions. Serum iron, transferrin saturation, serum ferritin, non-transferrin iron, and subcutaneous desferrioxamine-induced urinary iron excretion were measured. The results showed that even children with a limited number of transfusions had severe iron overload as indicated, in particular, by the raised serum ferritin levels and the high excretion rates after subcutaneous infusion of desferrioxamine. The desferrioxamine test was useful, even in very young children, in assessing response to chelation therapy thus enabling such treatment to be started early to prevent harm from iron overload.